Analysis of the Influence of Foreign Ownership on Financial Performance in the Telecommunication Industry - Ridwan (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
The impact of foreign ownership on the financial performance of telecommunications companies listed on the Indonesia Stock Exchange (IDX) is analyzed in this research. Using panel data from 2015 to 2023, key financial performance indicators such as Return on Assets (ROA), Return on Equity (ROE), and Profit Margin are examined. Moderating variables, including company size, leverage, and growth opportunities, are also considered. The analysis reveals a significant positive relationship between foreign ownership and financial performance. Companies with higher foreign ownership tend to show better asset utilization (ROA) and greater profitability (ROE). Additionally, moderating factors play a critical role: larger companies benefit more from foreign ownership, while high leverage negatively impacts the relationship between foreign ownership and financial performance. The findings suggest that managing leverage and seizing growth opportunities are key for maximizing the benefits of foreign investment. Encouraging foreign investment in Indonesia's telecommunications sector could enhance its competitiveness and overall performance. This research contributes to the understanding of foreign ownership and offers valuable insights for policymakers and business leaders in emerging markets.